Activation of a histone H1 kinase by tyrosine phosphorylation in v-src-transformed fibroblasts. - Sternberg, D W (1993)
Using anti-phosphotyrosine immunoaffinity chromatography, we have searched for serine/threonine kinases that are directly regulated by tyrosine phosphorylation in v-src-transformed rat 3Y1 fibroblasts. Tyrosine phosphoprotein preparations from v-src-transformed cells contain a kinase activity that phosphorylates histone H1 in vitro on serine residues and this activity is present at a 20-fold greater level than that in parental cell preparations. This activity elutes from a MonoQ FPLC column as a single peak and gel filtration chromatography suggests that the kinase has a molecular mass of approximately 55 kDa. Tyrosine phosphatase treatment inactivates the histone H1 kinase and this result indicates that the specific activity of the kinase is regulated by tyrosine phosphorylation. Experiments with cells transformed with a temperature-sensitive mutant of the v-src oncogene demonstrate that the tyrosine phosphorylation of the histone H1 kinase is an early event in v-src transformation. The kinase is distinct from known cdc2 family members that contain the PSTAIR motif, because the kinase can be separated almost completely from these proteins by immunoprecipitation with an antibody against p34cdc2. The profile of antibody reactivity and sensitivity to modulators of protein kinases suggests that this activity is distinct from known second messenger-regulated kinases and from previously characterized MAP kinases.